Explosion characteristics and chemical kinetics of blended LPG/DME clean fuel based on pyrolysis and oxidation mechanism model. (15th July 2022) - Zhang, Qi; Qian, Xinming; Li, Runzhi; Zhou, Gang; Sun, Yanlong; Ma, Yu; Kong, Yang
Highlights: The accuracy of the UCS 2016 model was verified by ignition delay time experiments. The theoretical AO and AFT under the effect of coupling multi-factors are revealed. DME has a greater enhancement effect on explosion overpressure than flame temperature. DME addition increases the degree of complete combustion reaction and explosion risk. DME addition increases the proportion of pyrolysis reaction path of LPG. Abstract: In order to reveal the explosion effects of blended LPG/DME at the microscopic level and to investigate its explosion mechanism, the UC San Diego 2016 C1-C4/DME pyrolysis and oxidation mechanism model was adopted to carry out a numerical investigation. The results show that the adiabatic overpressure (AO) and the adiabatic flame temperature (AFT) both increase and then decrease with the increase of the equivalence ratio for different DME blended ratios, and reach the maximum value in the slightly rich-fuel condition ( Φ = 1.0–1.1), theoretically, the maximum values reach 776 kPa and 2340 K respectively. Above two adiabatic parameters increase with rising DME blended ratio, and this enhancement effect is minimized at stoichiometric concentration. The AO is more susceptible to the enhancement effect of DME incorporation than the AFT. As the DME content increases, O2 consumption increases, newly added chemical reactions are used mainly to promote the explosion process, meanwhile the explosion temperature increases result from the increased proportion of pyrolysis reactions, all of which increase the explosion risk and hazards of blended LPG/DME clean fuel.